Pengaruh Service Quality, Price, Promotion, And Attractiveness Terhadap Repeat Purchase Rambak Pisang Pada Instagram Rampis.id (Studi Kasus Pada Pelanggan Rampis.id Kecamatan Lowokwaru) - Malinda, Elsa; Arifin, Rois; Saraswati, Ety (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The more rapid in the current era of globalization, the development of communication technology and the internet encourages a change in mindset in human life. One of the media used in people's lifestyles to communicate or do business is the internet media. The benefit of the internet is that it can be used as a facility to make transactions such as online shops. An online shop is a business network that is very broad and not limited by time and place. With the development of the use of the internet and digital applications, e-commerce has begun to be in great demand by capital owners. The existence of the internet makes it easy for people to shop anytime and anywhere online. The purpose of this study was to determine and analyze service quality, price, promotion, and attractiveness that simultaneously and partially influence repeat purchases for banana rambak customers in Lowokwaru sub-district on Instagram rampis.id. The population in this study were rampis.id banana rambak customers in Lowokwaru sub-district who had repurchased banana rambak at rampis.id so far. The approach method uses a non-probability sampling technique, namely purposive sampling which is a sample collection technique based on certain criteria using a questionnaire distributed to 100 respondents and using the SPSS analysis tool. The results showed that partially price and ease of use had a significant effect on purchasing decisions while electronic word of mouth did not have a significant effect on purchasing decisions. Simultaneously service quality, price, promotion, and attractiveness affect repeat purchases. Keywords : Service Quality, Price, promotion, Attractiveness, Repeat Purchase